An overview of RNA virus-encoded microRNAs - Xihan Li; Xiaoping Zou (ExRNA)
Abstract MicroRNAs (miRNAs) are a number of small non-coding RNAs playing a regulatory part in gene expression. Many virus-encoded miRNAs have been found, which manifests that viruses as well apply the basic pattern of gene regulation, however, mostly in viruses transcribed from double-stranded DNA genomes. It is still in dispute if RNA viruses could encode miRNAs because the excision of miRNA might result in the cleavage of viral RNA genome. We will focus on the miRNAs encoded by RNA virus and discuss their potential role in viral replication cycle and host cells.